THE MYSTERY OF THE RED SUITCASE: UNCOVERING THE CRIME OF HEINOUS MURDER WITH MUTILATION - Dhevtyana Kartikasari; Yogi Prasetyo; Ferry Irawan Febriansyah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research focuses on the study of criminal law regulation in the positive legal system in Indonesia, as well as assessing the extent to which these regulations cover the crime of mutilation. In addition, this study also analyzes the application of the provisions of article 340 of the Criminal Code in the case of the